Christian Missions and Social Welfare: Institutional Interventions and Societal Impact - Devasagayam, Victor Stalin A; Kumari, Amala Thanka J (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2025)
The Christian missions have been instrumental in formation of social welfare systems in various societies, particularly in the marginalized or vulnerable communities. Based on the theological concept of compassion, service and justice, these institutions historically had their mandate to go beyond evangelisation to education, health care, alleviation of poverty and community development. This paper is a critical examination of the institutional intervention of Christian missions in the area of social welfare and its overall influence on the society. Using qualitative and analytical approach, the paper follows the historical development of Christian social-service programs, the theological basis of these programs and splits the organisational structures of how these missions are run. Specific attention is paid to education, healthcare, social justice, and calamity relief as the key areas of intervention that help achieve human development and social inclusion. Other significant challenges and criticisms that the Christian mission organisations have faced are discussed in the paper, such as cultural sensitivity, practices of proselytization, and the challenge of sustainability. The study highlights the relevance of the Christian social welfare initiatives in the present-day development discourse by placing them in their context. The results show that Christian missions with ethical integrity and cooperation strategies are still important drivers of social change and community welfare.